Thermal management systems for batteries in electric vehicles: A recent review - Hafiz Muhammad Ali (Energy Reports, 2023)
IC engines in transportation sector are seen as a major cause of increasing air pollution. Electric Vehicles (EVs) are deemed as a green energy solution for pollution free future. The energy source of a modern-day EV is a Lithium ion battery pack. Temperature sensitivity is a major limitation for the lithium-ion battery performance and so the prevalent battery thermal management systems (BTMS) are reviewed in this study for practical implications. Firstly, the design considerations are analyzed to measure value of thermal safety and the international market potential is studied in this manuscript. Secondly, thermal stability analysis is drawn for thermal runaway situations, extreme weather conditions and aging phenomenon. The effect of sub-zero temperature, charging/discharging rates, failures caused by short circuiting, lack of temperature uniformity and mechanical deformation are also evaluated. In addition, the theoretical and experimental models of various battery thermal management strategies studied by different authors are compared for their effectiveness in hybrid and electric vehicles. The pinnacle of current review is to assess the upcoming challenges and substantial gaps in the approach of thermal management predicted by researchers and the latest practical methods used by EV manufacturers. Lastly, the optimization of BTMS is considered highly critical for the dominance of electric vehicles, by enhancement in lifespan and overall safety.